Respons Of Islamic Stock Markets To Monetary Policy Empirical Evidence from Indonesia - Rasyidin, Muhammad; Sulong, Zunaidah (Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
AbstractPurpose - The impact of stock market and capital formation on economic growth in Indonesia for the period of January 2015 â€“ May 2019. This paper examines a long-run equilibrium relation between stock market, capital formation and economic growth and other control variables.Method - This study uses autoregressive distributed lag (ARDL) model.Result - Findings revealed that none of the models was stationary at level but were all stationary at first difference. There is not a short run significant relationship between stock market, capital formation and economic growth in Indonesia. In the long run, capital formation has a significant positive association on economic growth and a negative non-significant relationship between stock market and economic growth in Indonesia.Implication - This research is useful to know the response of Sharia market to monetary policy instruments in Indonesia so that the Sharia stock market strategy is potentially developing in the future to encourage the achievement of characteristics such as An alternative source of financing and investment for economic actors and able to facilitate risk mitigation needs for market participants and able to drive the efficiency of transactions in the market through the improvement of the quality of stock market infrastructure Sharia. Â Originality - The update of this research is response of Sharia stock market response to monetary policy instruments in Indonesia that are researched using ARDL models.